Voluntary intake of prairie hay contaminated with sericea lespedeza (lespedeza cuneata) by beef cows - G.J. Eckerle; L.A. Pacheco; K. C. Olson; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2011)
Sericea lespedeza (Lespedeza cuneata) is a noxious weed that infests approximately 600,000 acres of native tallgrass range in the Kansas Flint Hills. Intake of sericea lespedeza by grazing beef cattle is poor due to the presence of condensed tannins in the plant. Condensed tannins reduce protein digestion by beef cattle and may decrease plant palatability because of their astringence. Prolific seed production, in combination with little or no grazing pressure, has contributed to the rapid spread of sericea lespedeza in the Flint Hills. Increasing grazing pressure on sericea lespedeza may reduce seed production and slow its invasion; however, the difficulties associated with measurement of intake by grazing beef cattle have hampered development of workable research models. Detailed study of the appetite- suppressing effects of sericea lespedeza under controlled conditions is essential to develop appropriate strategies to increase grazing pressure on this plant. Such information could lead to a degree of biological control of this noxious weed using the most economically important grazer (i.e., beef cattle) in the Flint Hills.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen& #x27; s Day; 2011; Beef; Intake; Sericea Lespedeza; Prairie hay